Assessing the Impact of Kidnapping and Banditry on Students’ Academic Performance in Nigeria: Implications for Education and Security Policies - Omojemite, Matthew Damilola (Journal of Ecohumanism, 2025)
This study investigates the incidence of kidnapping and banditry on students’ academic performance with implications for education and security policies in Nigeria. Descriptive survey research design has been adopted for this study to be carried out among school students and university students in selected states: Ondo, Kogi, Bauchi, Kaduna, Anambra, and Edo. It had a target population of all students in the country’s senior and tertiary institutions. Stratified random sampling was conducted to make a random population of 6000 out of these three tiers, into which each student belonged. The data collection instruments included the IKB-SAPQ developed and validated by experts in education and security studies. Its reliability was established with a Cronbach’s alpha coefficient of 0.85. The tool was administered with the collaboration of school authorities and trained research assistants, thus yielding a very high response rate. Descriptive and inferential statistics, such as percentages, means, and ANOVA, were used in the analysis to ascertain the magnitude and variation of these effects. Results showed that kidnapping and banditry significantly disrupt students’ academic performance through poor attendance, psychosocial disturbances, and decreased motivation. More than 65% of the students had concentration problems and disruptions of school work, while 70% showed increased anxiety and fear. The study recommends improving security in schools, safety at the community level, and increasing psychological support for affected studentsz. Furthermore, the government and educational stakeholders have to work together to enact policies that would address these root causes of insecurity and create a conducive environment for learning.